Symptom or faecal immunochemical test based referral criteria for colorectal cancer detection in symptomatic patients: a diagnostic tests study - Herrero, Jesús-Miguel (BMC Gastroenterol, 2018)
BACKGROUND: Symptom based referral criteria for colorectal cancer (CRC) detection are the cornerstone of the strategy to improve prognosis in CRC. In 2017, the National Institute for Health and Care Excellence (NICE) updated their referral criteria (2017 NG12). Recently, several studies have evaluated the faecal haemoglobin (f-Hb) concentration in this setting. The aim of this study is to evaluate the diagnostic accuracy of the 2017 NG12 referral criteria and to compare them with the CG27 referral criteria, the f-Hb concentration and two f-Hb based prediction model: COLONPREDICT and FAST Score. METHODS: This is a post-hoc diagnostic test study performed within the COLONPREDICT study database (1572 patients, CRC prevalence 13.6%). We assessed symptoms, the 2017 NG12 and CG27 referral criteria and determined the f-Hb before performing a colonoscopy. We compared the discriminatory ability using the area under the curve (AUC) and the sensitivity and specificity at pre-stablished thresholds with the McNemar’s test. RESULTS: The 2017 NG12 referral criteria discriminatory ability (AUC 0.53; 95% confidence interval- CI 0.49–0.57) was inferior to the CG27 version (AUC 0.59; 95% CI 0.55–0.63; p = 0.01), the f-Hb concentration (AUC 0.86; 95% CI 0.84–0-89; p < 0.001), the COLONPREDICT Score (AUC 0.92; 95% CI 0.91–0.94; p < 0.001) or the FAST Score (AUC 0.87; 95% CI 0.85–0.89; p < 0.001). The number of patients meeting each criteria were as follows: 2017 NG12 and CG27 = 94.1% and 52.2%; f-Hb ≥20 and ≥ 10 μg/g faeces = 38.6 and 44.3%; COLONPREDICT Score ≥ 5.6 and ≥ 3.2 = 29.4 and 63.2% and FAST Score ≥ 4.50 and ≥ 2.12 = 37.1 and 87.0%. The 2017 NG12 criteria were more sensitive (100%) than the CG27 criteria (68.2%), the f-Hb (≥20 μg/g) (91.2%), the f-Hb (≥10 μg/g) (93.5%), the COLONPREDICT Score (≥5.6) (90.1%) and the FAST Score (≥4.50) (89.8%) (p ≤ 0.001) and equivalent to the COLONPREDICT Score (≥3.5) (99.5%) or the FAST Score (≥2.12) (100.0%) (p = 1). However, their specificity (6.8%) was significantly lower than any of the evaluated criteria (50.3%, 69.6%, 63.4%, 78.7%, 45.8%, 71.3%, 13.9%; p < 0.001). CONCLUSION: Referral criteria based on f-Hb measurement, either as a single test or within prediction models, are more accurate than symptom-based referral criteria for CRC detection in symptomatic patients.